Analisis Hasil Audit Pemerintahan dan Tingkat Korupsi Pemerintahan Provinsi di Indonesia - Rini, Rini; Damiati, Liska (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
Agency theory assumes that there are many information asymmetries between the agents (local government) who have direct access to information by the principals (the public). The existence of information asymmetry that allows the occurrence of corruption by local government. Government auditing is believed to affect the level of local government corruption. The purpose of this research is to analyze the influence of government auditing result such as audit opinion, audit finding, and audit rectification to the level of provincial government corruption in Indonesia.This research uses secondary data from the audit result of Badan Pemeriksa Keuangan Republik Indonesia, Badan Pusat Statistik and the prosecutor annual reports. This research uses purposive sampling and using multiple linear regression analysis. The study shows that partially, audit rectification has negative effect on corruption level, audit finding and audit opinion has no effect on corruption level. Simultaneously, these variables have significant influence on corruption level.